Cloud patterns for mobile collaborative applications. (2017) - Guetmi, Nadir; Imine, Abdessamad
Deploying collaborative applications (e.g., group editors) over mobile devices is problematic because these devices will always be resource-poor and with unstable connectivity and constrained energy. To overcome these limitations, one straightforward solution is to leverage mobile collaboration via the cloud. This emerged model relies on virtualisation for efficient and flexible use of hardware assets and software services over a network without requiring user intervention. However, designing collaborative applications with flexibility and reusability has become a hot topic in mobile cloud computing as no mature models have been proposed yet. In this paper, we describe cloud patterns (i.e., extension of classic design patterns) focusing on the description of mobile real time data sharing through the cloud. Our design model consists of two levels: the first one provides self-protocol to create clones of mobile devices, manage users' groups and recover failed clones in the cloud. As for the second level, it supports group collaboration mechanisms for data sharing between mobile users via their clones. Our patterns have been used as a basis for the design of: 1) MidBox a platform for supporting mobile collaboration over a private cloud; 2) OptiCloud a cloud service for scalable real-time editing works.